2014
DOI: 10.1186/1471-2458-14-241
|View full text |Cite
|
Sign up to set email alerts
|

Workplace gender composition and psychological distress: the importance of the psychosocial work environment

Abstract: BackgroundHealth consequences of the gender segregated labour market have previously been demonstrated in the light of gender composition of occupations and workplaces, with somewhat mixed results. Associations between the gender composition and health status have been suggested to be shaped by the psychosocial work environment. The present study aims to analyse how workplace gender composition is related to psychological distress and to explore the importance of the psychosocial work environment for psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
9
0
3
Order By: Relevance
“…Il se pourrait aussi que le secteur tertiaire, qui contient une proportion importante de femmes, convienne moins à certains hommes qui se retrouvent de fait dans des univers de travail moins masculins et possiblement moins propices à leur épanouissement personnel. Selon une étude récente, la mixité de genre à l'intérieur d'un environnement de travail serait associée à la détresse psychologique 28 .…”
Section: Discussionunclassified
“…Il se pourrait aussi que le secteur tertiaire, qui contient une proportion importante de femmes, convienne moins à certains hommes qui se retrouvent de fait dans des univers de travail moins masculins et possiblement moins propices à leur épanouissement personnel. Selon une étude récente, la mixité de genre à l'intérieur d'un environnement de travail serait associée à la détresse psychologique 28 .…”
Section: Discussionunclassified
“…Although the higher odds of mild to severe depression in the most female-dominated occupations were attenuated by the inclusion of the psychosocial work factors, they remained significant, suggesting that most of the variation in mild to severe depression between strata of occupational gender composition are explained by other factors. We cannot rule out the possibility that men with a history of mental-health problems end up in the most female-dominated occupations, an association that has previously been suggested by Swedish and Danish researchers [15,17]. Among men with high education, higher odds of mild to severe depression were reported particularly in professions with >20–40% and >60–80% women compared to professions with 0–20% women.…”
Section: Discussionmentioning
confidence: 80%
“…Among men with high education, higher odds of mild to severe depression were reported particularly in professions with >20–40% and >60–80% women compared to professions with 0–20% women. In a study based on the Northern Swedish Cohort, Elwér et al found that psychological distress in both genders was more pronounced in gender-integrated than in gender-segregated workplaces; psychosocial work factors could not explain the difference in their study either [15]. The occupational stratum with >20–40% women consisted of, for example, engineers, police officers, computing professionals, estate agents and organisational analysts, and the stratum with >60–80% women of, for example, public-service administrative professionals, primary-education teaching professionals and banking associate professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since workplace gender composition was found to be related to psychological distress in recent research (e.g., Elwér, Johansson, & Hammarström, 2014), percentage of female workers was entered as a workplace covariate. This information was collected from the human resources department in each company.…”
Section: Methodsmentioning
confidence: 99%